Developing an Action Plan for the Kenya Drought Watch System and Reviewing Triggers and Thresholds for Drought Anticipatory Action - Okoth, Vincet; Ouma, Jully; Kinyua, Jason; Amdihun, Ahmed; Demissie, Teferi (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
Droughts have become more frequent and severe in Kenya and across East Africa, exacerbating food insecurity, water scarcity, and economic instability. To address these challenges, robust drought monitoring and early warning systems must be developed, as well as anticipatory actions that can mitigate the impact of droughts before they occur. ICPAC, in collaboration with key partners such as AICCRA and the Kenyan government, planned to support the development of a National Drought Watch System, which will provide real-time data and analysis on drought conditions and early warning systems. Initiatives such as ForPAc, INFORM, AstroCAST, IARP, and FbF for food security(F4S) have led to the development of drought forecasts and triggers and thresholds to support the co-development of AA in Kenya and the region. The Kenya National Drought Watch System is envisioned as a foundational model for other IGAD member states, showcasing the best drought monitoring and response practices. It also leverages protocols for drought triggers and thresholds developed by organizations such as ICPAC, WFP, FAO, the Red Cross, NDOC, KMD, and NDMA. By reviewing and refining these protocols, the system aims to enhance resilience to climate variability nationally and regionally. The workshop aimed to create a comprehensive action plan for the Kenya Drought Watch System (KDWS), ensuring consistency with the regional East Africa Drought Watch systems and a detailed review of the national triggers and thresholds for Anticipatory Action (AA).